3D printed scaffolds: Challenges toward developing relevant cellular in vitro models - Beatriz Molina-Martínez; Luis M. Liz-Marzán (Biomaterials and Biosystems, 2022)
Three-dimensional (3D) cell culture technology has rapidly emerged, as a result of the increasing demand for improved in vitro systems that better resemble human physiology. Promising microphysiological systems have been fabricated by combining complex 3D culture with 3D-printing technologies. These models overperform existing in vitro systems regarding potential for biofabrication and predictive power. However, most systems under development do not ultimately find a long-term application. We provide herein an overview of the challenges to be considered when developing 3D in vitro systems by means of printed scaffolds, as well as some of the limitations of existing models.